2018
DOI: 10.1007/s00484-018-1533-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of climatic variations on the reproductive success of Gentiana lutea L. in a Mediterranean mountain area

Abstract: Increases in temperature have been predicted and reported for the Mediterranean mountain ranges due to global warming and this phenomenon is expected to have profound consequences on biodiversity and ecosystem functioning. We hereby present the case of Gentiana lutea L. subsp. lutea, a rhizomatous long-lived plant living in Central-Southern Europe, which is at the edge of its ecological and distributional range in Sardinia. Concretely, we analysed the reproductive success experienced during three phenological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…This could indicate that these populations, which are located at lower altitudes and at the edge of its distributional and ecological range, would be more threatened, if facing shorter winters. Seed germination results obtained in this work, in particular, the detection that seeds of G. lutea needed at the least 60 days of cold temperature to remove dormancy, are in agreement with previous studies (Fois et al, 2016;Cuena-Lombraña et al, 2018b) which reported that the most affected localities are those that are present at the lowest altitudes. Therefore, with the results presented here, it is possible to affirm that, while also considering the germination capacity of the seeds, climate warming will likely first affect the localities of G. lutea at lower altitudes.…”
Section: Discussion Effect Of Reduction Of Cold Stratification Periodsupporting
confidence: 92%
“…This could indicate that these populations, which are located at lower altitudes and at the edge of its distributional and ecological range, would be more threatened, if facing shorter winters. Seed germination results obtained in this work, in particular, the detection that seeds of G. lutea needed at the least 60 days of cold temperature to remove dormancy, are in agreement with previous studies (Fois et al, 2016;Cuena-Lombraña et al, 2018b) which reported that the most affected localities are those that are present at the lowest altitudes. Therefore, with the results presented here, it is possible to affirm that, while also considering the germination capacity of the seeds, climate warming will likely first affect the localities of G. lutea at lower altitudes.…”
Section: Discussion Effect Of Reduction Of Cold Stratification Periodsupporting
confidence: 92%
“…Climate change is known as a major threat to species survival and the integrity of ecosystems worldwide [ 1 , 2 ]. Numerous studies have documented the effects of climate change on biodiversity during the twentieth century, including alterations in distribution and phenology, and increases in extinction risk for many species [ 3 5 ]. Given these changes, assessments of the impacts of climate change on species’ geographic distributions are necessary to reveal the extent of risk and to permit the design of appropriate conservation programs for species.…”
Section: Introductionmentioning
confidence: 99%
“…Transformative stress can be experienced by biological systems as a result of high intensity-low frequency climate events, low intensity-high frequency climate events, or a particular sequencing of these events. Yet, ecological responses are typically modeled as a function of mean climate conditions [102,103] , with few models examining the implications of more short-lived climatic extremes [104][105][106]. The failure to incorporate extreme events into ecological models can create an inaccurate or incomplete understanding of future ecological conditions [6,103], since ecosystems respond to both changes in mean environmental conditions, as well as to extreme events [107,108].…”
Section: Relevance Of Extreme Climate Events In Driving Biological Impactsmentioning
confidence: 99%